PENGARUH MINUMAN JAHE MERAH (ZINGIBER OFFCINALE ROSCOE VAR. RUBRUM) TERHADAP PENURUNAN SKALA NYERI DISMENOREA PRIMER PADA MAHASISWI DI PROGRAM STUDI S1 FARMASI UNIVERSITAS IMELDA MEDAN - Samgryce Siagian, Hartika; Mariyana Ritonga (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
Dysmenorrhoea is a gynecological complaint caused by an imbalance of the progesterone hormone in the blood, which causes pain and is most often characterized by menstrual cramps. A safe way to treat dysmenorrhoea is by boiling helbal, which is red ginger drink. The purpose of this study was to determine the effect of red ginger drink on reducing the scale of dysmenorrhoea pain on students at the University of Imelda Medan.This research method uses quantitative research with a descriptive design. The number of respondents in this study were 42 people using the sampling technique with the Slovin formula. The instrument used was a questionnaire with yes or no answer choices. The results of the study of 42 respondents, the majority who experienced pain or dysmenorrhoea, were 32 respondents with a percentage (92.9%). And the effect of red ginger drink on the dysmenorrhoea pain scale was 29 respondents with a percentage (69.0%). The effect of red ginger drink on the primary dysmenorrhoea pain scale is sufficient.